2011
DOI: 10.1002/da.20880
|View full text |Cite
|
Sign up to set email alerts
|

Tools for translational neuroscience: PTSD is associated with heightened fear responses using acoustic startle but not skin conductance measures

Abstract: Background: Posttraumatic stress disorder (PTSD) patients show heightened fear responses to trauma reminders and an inability to inhibit fear in the presence of safety reminders. Brain imaging studies suggest that this is in part due to amygdala over-reactivity as well as deficient top-down cortical inhibition of the amygdala. Consistent with these findings, previous studies, using fear-potentiated startle (FPS), have shown exaggerated startle and deficits in fear inhibition in PTSD participants. However, many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 61 publications
(118 reference statements)
6
97
1
Order By: Relevance
“…Startle responses and self-reported distress were strongly affected by trait anxiety, while UCS expectancy learning was only mildly affected, and SCR not at all. These findings suggest that the contingency measures may not be as sensitive as the affective responses to vulnerability differences in fear expression (see for similar results in PTSD patients Glover et al, 2011). As noted before, SCR appears to be a function of both arousal and contingency learning (Bradley and Lang, 2000;Hamm and Weike, 2005), while the startle response, on the other hand, is modulated by arousal and negative valence (Lang, 1995), guided by a different neurobiological system (Davis, 2006).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Startle responses and self-reported distress were strongly affected by trait anxiety, while UCS expectancy learning was only mildly affected, and SCR not at all. These findings suggest that the contingency measures may not be as sensitive as the affective responses to vulnerability differences in fear expression (see for similar results in PTSD patients Glover et al, 2011). As noted before, SCR appears to be a function of both arousal and contingency learning (Bradley and Lang, 2000;Hamm and Weike, 2005), while the startle response, on the other hand, is modulated by arousal and negative valence (Lang, 1995), guided by a different neurobiological system (Davis, 2006).…”
Section: Discussionmentioning
confidence: 64%
“…The results of these discriminative fear conditioning studies indicate evidence for both deficient safety learning and overgeneralization of fear. For instance, several studies have shown that patients with anxiety disorders generally exhibit elevated fear responding during fear acquisition to the unreinforced stimulus (CS2 − ) (Galimberti et al, 2010;Grillon and Morgan, 1999;Lissek et al, 2009;Orr et al, 2000;Peri et al, 2000) or to both the threat and safety stimulus (Glover et al, 2011). Also, anxiety patients have demonstrated delayed reduction of fear responding to either the threat stimulus or to both the threat and safety stimulus during extinction learning Michael et al, 2007;Norrholm et al, 2011;Orr et al, 2006;Pitman and Orr, 1986), reduced retention of extinction (Milad et al, 2008) and impaired fear inhibition (Jovanovic et al, 2009(Jovanovic et al, , 2010.…”
Section: Introductionmentioning
confidence: 97%
“…By virtue of ensuing fast responding to novel potentially threatening stimuli fear generalization is functional, but it can turn into maladaptive behaviour when nonthreatening stimuli or contexts are inappropriately treated as harmful. Maladaptive fear generalization is indeed characteristic for anxiety disorders and PTSD (Glover et al, 2011;Grillon & Morgan, 1999;Lissek et al, 2005Lissek et al, , 2009Lissek et al, , 2010Lissek et al, , 2014Orr et al, 2000;Peri, BeanShakhar, Orr, & Shalev, 2000) and may explain the transition from normal to abnormal fear (Rosen & Schulkin, 1998). For example, when somebody has been bitten by a pit-bull, it is entirely functional to develop a fear for this dog and even if the learned fear generalizes to other similar dogs, we consider this as a functional fear generalization.…”
Section: Generalization and Contextualization Of Fear Memorymentioning
confidence: 92%
“…Ressler et al (4) recorded startle responses to the CS1 and CS2, whereas in the present study (owing to the scanner environment), only SCRs were used. This methodologic difference might have contributed to discrepancies in the results on the relationship of the PAC1-R polymorphism and cued fear conditioning because acoustic startle responses could potentially be more sensitive to detect subtle differences (35). We found only a genetic influence on hippocampal activity, a brain structure not essential for simple cue conditioning paradigms (16).…”
Section: Discussionmentioning
confidence: 85%